2014
DOI: 10.1093/socrel/sru040
|View full text |Cite
|
Sign up to set email alerts
|

The Hallmarks of Righteous Women: Gendered Background Expectations in The Church of Jesus Christ of Latter-Day Saints

Abstract: In this article, we examine how leaders of The Church of Jesus Christ of Latter-day Saints (LDS or Mormon) collaborated with some Mormon women to construct gendered background expectations. Based on LDS archival materials, we analyze how LDS leaders and their representatives embedded specific notions of what it means to be a woman into the institutional and theological structure of the religion by (1) defining womanhood and (2) teaching femininity in ways that sanctified gender inequality. In doing so, LDS lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Although the discursive elaboration of gender is ubiquitous throughout the LDS archives (see Sumerau and Cragun ), LDS elites did not explicitly align these notions with homosexuality until the 1980s. Considering that LDS elites mobilized these thoughts during the 1970s in response to feminist campaigns for the Equal Rights Amendment and abortion rights (Cragun and Phillips ; Williams ), it is curious that they were not applied to homosexuality earlier.…”
Section: Problematizing Homosexualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the discursive elaboration of gender is ubiquitous throughout the LDS archives (see Sumerau and Cragun ), LDS elites did not explicitly align these notions with homosexuality until the 1980s. Considering that LDS elites mobilized these thoughts during the 1970s in response to feminist campaigns for the Equal Rights Amendment and abortion rights (Cragun and Phillips ; Williams ), it is curious that they were not applied to homosexuality earlier.…”
Section: Problematizing Homosexualitymentioning
confidence: 99%
“…In fact, the earliest use of this discursive strategy—as well as the only time LDS discourse on homosexuality spiked in the 1980s (see Figure )—coincided with the growth of support groups for gay and lesbian Mormons and the establishment of the Restoration Church of Jesus Christ, which promoted both an explicitly lesbian and gay interpretation of Mormonism and the extension of religious leadership to Mormon women (see Phillips 2005 for a brief history). Although LDS elites never explicitly mentioned either of these events in their statements, they began constructing homosexuality as a violation of divinely inspired gender norms immediately following these episodes, and have utilized these discourses as recently as 2014 court filings opposing same‐sex marriage (see Sumerau and Cragun ).…”
Section: Problematizing Homosexualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that researchers have noted widespread expansion of pornography throughout American society in recent years (Attwood, 2011) as well as increased rates of religious exiting (i.e., apostasy) from the Mormon Church since 1989 (see Phillips and Cragun, 2013), LDS leaders could be responding to potential failings of their other lessons regarding sexual morals. Even if this were the case, however, increased religious exiting among Mormons is likely due to multiple social factors including but not limited to other sexual (see Sumerau and Cragun, 2014a) and gender (see Sumerau and Cragun, 2014b) conflicts taking place within the church over the last decade. On the other hand, research has shown that overall religious affiliation in the USA has also been declining in recent years (Funk and Smith, 2012) and that pornographic expansion has occurred throughout the world over the last 40 years (Ezzell, 2008), which means they could simply be responding to broader religious and sexual patterns taking place throughout the entirety of the years captured in our data.…”
Section: Seeking Spiritual Treatmentmentioning
confidence: 99%
“…Since its inception, sociology has grappled with the influence of varied deities (i.e., gods, goddesses, supreme beings, and other sacred symbols) upon people (see, e.g., Durkheim [1912] ; Marx [1843] ; Weber [1922] ). Researchers have documented, for example, ways people adopt and adjust interactional presentations in relation to deities of many sorts (see, e.g., Dunn and Creek ; Mead ; Wolkomir ), ways beliefs in varied deities influence social organizations, institutions, and traditions (see, e.g., Bush ; Robinson and Spivey ; Sumerau and Cragun ), and ways ideologies rooted in belief in a certain deity shape racial, class, gendered, and sexual patterns of inequality (see, e.g., Collins ; McQueeney ; Sumerau ). While these studies have expanded our understanding of the ways people utilize deities to make sense of their experiences, they have thus far left unexplored the social construction of such phenomena.…”
mentioning
confidence: 99%